PENGEMBANGAN MODUL FISIKA BUMI-ANTARIKSA UNTUK MENINGKATKAN PRESTASI BELAJAR MAHASISWA PRODI PENDIDIKAN FISIKA FKIP UNLAM - Zainuddin,, Zainuddin; Mustikawati, Mustikawati; Suyidno, Suyidno (Jurnal Vidya Karya, 2012)
The developmental research objective is to produce the module of outer space physics (Fisika Bumi Antariksa or FBA) that is suitbale and effective to increase the students’ achievment of Physics Education in Faculty Teacher Training and Education, Lambung Mangkurat University. The developmental method used Four D Mode covering define, design, develop, and disseminate. The subject of research is 33 students who took the outer space physics lecture for odd semester in 2011/2012. The data collection technique used the evaluation of suitability, questionnaire, and test. The tecnique of data analysis is qualitative and descriptive. The result of research stated that (1) the module of outer space physics is suitable for learning material relating to content, language, and dilivery; (2) the students’ achievment is good because 9% of the students total number got “A” meaning very satisfying, 45% of them got “B” meaning satisfying, 27% of them got “C” meaning enough satisfying; and (3) the students responded positively to the use of the module of outer space physics in teaching learning activity. In a word, the module of outer space physics is suitable and effective to increase the students’ achievment of Physics Education in Faculty Teacher Training and Education, Lambung Mangkurat University.